Exploring the Impact of Artificial Intelligence on Women's Empowerment: A Comprehensive Survey - Shahbazi, Hafizullah; Hakimi, Musawer; Ulusi, Helena; Rahimi, Behnaz; Quraishi, Tamanna (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
Artificial intelligence (AI) can significantly empower women and promote gender equality globally. However, to effectively utilize AI to promote women's empowerment, it is crucial to comprehend its influence, possibilities, and difficulties comprehensively. This study examines the various aspects of how AI contributes to the advancement of women's empowerment. It explores the extent to which AI is integrated into initiatives aimed at empowering women, the perceived impact of AI on women's empowerment on a global scale, and the obstacles women face in accessing AI opportunities. An integrated research methodology, including surveys and literature evaluation, was utilized to collect data from a diverse sample of 88 people. The results indicate a substantial degree of AI incorporation in projects aimed at empowering women, with varying perspectives on the impact of AI. Additionally, the study revealed difficulties in accessing AI opportunities and observed differing levels of knowledge among women. This study highlights the significance of ethical issues and inclusive policies in utilizing AI to promote women's empowerment. The findings provide significant knowledge for policymakers, researchers, and practitioners who aim to utilize AI's revolutionary capacity to promote gender equality and empower women globally.